2020
DOI: 10.1177/0017896920911675
|View full text |Cite
|
Sign up to set email alerts
|

FAST 112 HEROES: A kindergarten-based educational stroke intervention for the whole family

Abstract: Background: Stroke is a worldwide leading cause of disability, and around 50 million people are affected by stroke annually. Public stroke educational and awareness programmes can make a great deal of difference. Young children are in key position to seek urgent medical care if grandparents suffer a stroke, as grandparents are often their secondary caretakers. Objective: The objective of the current study was to design an educational intervention targeting children and, in parallel, directly involve extended f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…In earlier work, we showed that children 5–7 years of age recalled stroke information immediately after programme implementation and remembered it approximately one month later (Tsakpounidou et al, 2020). In this study, we found that kindergarteners can also serve as conduits of stroke information to their extended families.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In earlier work, we showed that children 5–7 years of age recalled stroke information immediately after programme implementation and remembered it approximately one month later (Tsakpounidou et al, 2020). In this study, we found that kindergarteners can also serve as conduits of stroke information to their extended families.…”
Section: Discussionmentioning
confidence: 96%
“…Educating children at a young age helps crystallise knowledge in long-term memory, aiding its recall during an emergency. The FAST 112 Heroes educational programme helps preschool children identify three cardinal signs of stroke and learn how to respond appropriately in the event of a stroke (Tsakpounidou et al, 2019(Tsakpounidou et al, , 2020. In the programme, a cartoon character, Timmy, responds quickly in a way that younger children aged 5-7 years can imitate.…”
Section: Introductionmentioning
confidence: 99%
“…In order to check the validity of the questionnaire, we conducted a focus group with members of the "Super Grand League Team, " a team of professionals that involves kindergarten teachers, speech language pathologists, psychologists, and special education teachers (12). The focus group unanimously agreed regarding the content of the questions.…”
Section: Methodsmentioning
confidence: 99%
“…Educational interventions about stroke, such as "Hip Hop Stroke" (10) and "Stroke 112" (11) are estimated to be effective for both children and family members through in-house communication. In this regard, the FAST (Face, Arms, Speech, Time) 112 Heroes educational program (12), is unique in that it addresses preschool children who are still in the process of developing communication and learning skills. Creating automatic knowledge gains at this age, by increasing the recognition of stroke symptoms, will lead to increasing stroke knowledge to the children's parents (13).…”
Section: Introductionmentioning
confidence: 99%
“…FAST Heroes program differs significantly from other programs because it targets kindergarten children from the age of 4 years old, and it aims to educate the extended family, outside the nuclear family, about stroke symptom recognition and appropriate course of action. In this way, stroke knowledge can be delivered to the broader community ( 31 , 32 ). The element that is added in this study is the transference of stroke knowledge from children to their parents within an international setting.…”
Section: Introductionmentioning
confidence: 99%